The role of semantic stimuli in enhancing creativity in art and design education - Yu, Yang; Nagai, Yukari (Frontiers in Education, 2025)
IntroductionPrevious studies have emphasized the role of verbal stimuli in fostering creativity, yet a systematic exploration of semantic stimuli within the context of art and design education remains scarce. This study aims to empirically investigate the effects of different types of semantic stimuli, the proactive application of creativity evaluation criteria, and the role of individual differences in the process of generating design ideas.MethodsA semantic stimulation intervention using verbal stimuli was conducted with 409 university students from the School of Art and Design and the School of International Education. Verbal semantic stimuli, unlike visual or auditory forms, offer a controllable and cognitively integrative format suitable for precise application in design education. First, expert commentary terms were introduced as semantic stimulus materials to enhance their relevance and effectiveness in educational settings. Second, creativity evaluation criteria were transformed from traditional outcome assessment tools into thinking guidance tools, applied at the early stages of the design process.ResultsBoth abstract and concrete semantic terms were found to effectively stimulate students’ creative thinking. Creativity evaluation criteria were shown to function not only as tools for post-project assessment but also as guides for creative thinking during the early stages of design. Chi-square tests revealed that individual differences, such as participants’ educational background and major, significantly influenced their preferences for using semantic stimuli and their performance in idea generation.DiscussionThis study provides a practical semantic stimulation method for art and design education, promoting a shift in teaching models from experience-driven approaches to rational guidance. It also offers a new form of support for design practice during the concept generation phase.